2008
DOI: 10.1016/j.neulet.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of whole-genome linkage scans for intracranial aneurysm

Abstract: Background and Purpose: Genetic predisposition likely plays an important role in the development of intracranial aneurysms. We carried out a genome search meta-analysis to identified loci associated with intracranial aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Similarly, other candidates related to smooth muscle contractility and function have been identified in individuals with familial TAAs13,19 and therefore might be plausible candidates in the broader phenotype. We did not find evidence of linkage to these loci in the current analysis nor was there evidence of linkage in the genomewide linkage analysis of the FIA population overall5 or in a recent meta-analysis of other genomewide linkage studies in IA17 supporting heterogeneity in genetic determinants of these complex disorders. Further specific investigations into these candidate genes may be warranted in this population.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Similarly, other candidates related to smooth muscle contractility and function have been identified in individuals with familial TAAs13,19 and therefore might be plausible candidates in the broader phenotype. We did not find evidence of linkage to these loci in the current analysis nor was there evidence of linkage in the genomewide linkage analysis of the FIA population overall5 or in a recent meta-analysis of other genomewide linkage studies in IA17 supporting heterogeneity in genetic determinants of these complex disorders. Further specific investigations into these candidate genes may be warranted in this population.…”
Section: Discussioncontrasting
confidence: 68%
“…It is approximately 10 Mbp from Vaughan et al (117 Mbp to 120 Mbp); however, key recombinants resulted in a very narrow confidence interval (1.1 cM). This same region was associated with the IA phenotype in a meta-analysis with a probability value of 0.012 17. As outlined in a recent analysis of loci identified in IA, AAA, and TAA, the 11q24 locus is a relatively large block with many genes, none of which are currently implicated in disease pathophysiology 12.…”
Section: Discussionmentioning
confidence: 82%
“…A variety of genes or chromosomal regions have been identified in both familial and sporadic cases of IAs. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] In linkage studies, regions on chromosomes 1p34.3-p36.13, 7q11, 19q13.3, and Xp22 have been associated with IAs. Genome-wide association studies identified replicated associations on chromosome 4q31.23 (EDNRA), 8q12.1 (SOX17), 9p213 (CDKN2A/CDKN2B/CDKN2BAS), 10q24.32 (CNNM2), 12q22, 13q13.1 (KL/STARD13), 18q11.2 (RBBP8), and 20p12.1, with the strongest evidence for the CDKN2BAS and SOX17 genes.…”
Section: Family History and Geneticsmentioning
confidence: 99%
“…(Farnham et al 2004; Foroud et al 2008, 2009; Kim et al 2011; Mineharu et al 2007; Nahed et al 2005; Olson et al 2002; Onda et al 2001; Ozturk et al 2006; Roos et al 2004; Ruigrok et al 2008; Santiago-Sim et al 2009; van der Voet et al 2004; Verlaan et al 2006; Yamada et al 2004). A recent meta-analysis of five familial mapping studies revealed an additional two loci in linkage disequilibrium with FIA, 3q27.3-3qter and 17p12-q21.33 (Biros and Golledge 2008). A SNP association study aimed at replicating loci previously flagged by linkage analysis confirmed the association at 14q23 (found by (Ozturk et al 2006)) in a cohort of 266 affected and 288 unaffected Japanese individuals (Mineharu et al 2008).…”
Section: Family Mapping Studiesmentioning
confidence: 99%